2014
DOI: 10.1039/c4ra08322a
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-inspired ultrathin film on oxidized Ti–6Al–4V surface for enhanced BMSC activities and antibacterial capability

Abstract: To improve the biocompatibility and antibacterial capability of thermally oxidized Ti-6Al-4V, an ultrathin alginate/chitosan film that contains nano-silver was constructed through mussel-inspired poly(dopamine). The hybrid structure was successfully fabricated on the Ti-6Al-4V surface without deterioration of the rough surface induced by thermal oxidation (TO). The hybrid surface was characterized by the use of contact angle goniometry (CAG), atomic force microscopy (AFM), scanning electron microscopy (SEM), X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Our previous study demonstrated that the crosslinker dopamine-N'N'-methylene-bis-acrylamide (dopa-MBA) could incorporate Ppy into a methyl acrylic anhydride (MA)-gelatin (GelMA)/poly (ethylene glycol) diacrylate (PEGDA) cryogel, which displayed good biocompatibility and high conductivity 31 . Dopamine, inspired by mussel adhesive protein, generated interest in the regenerative medicine field due to its excellent adhesive and crosslinking function 32 - 36 . When dopamine reacts with MBA through Michael addition reaction to form a double-bond crosslinker, this mussel-inspired crosslinker could quickly graft onto the GelMA/polycaprolactone (GelMA/PCL) nanofibers by photoinitiators 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that the crosslinker dopamine-N'N'-methylene-bis-acrylamide (dopa-MBA) could incorporate Ppy into a methyl acrylic anhydride (MA)-gelatin (GelMA)/poly (ethylene glycol) diacrylate (PEGDA) cryogel, which displayed good biocompatibility and high conductivity 31 . Dopamine, inspired by mussel adhesive protein, generated interest in the regenerative medicine field due to its excellent adhesive and crosslinking function 32 - 36 . When dopamine reacts with MBA through Michael addition reaction to form a double-bond crosslinker, this mussel-inspired crosslinker could quickly graft onto the GelMA/polycaprolactone (GelMA/PCL) nanofibers by photoinitiators 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…29 Bone marrow mesenchymal stromal cells (BMSCs) have recently been widely explored for chondrogenic differentiation in cartilage repair. [30][31][32][33][34][35][36][37][38][39][40] In our study, for chondrogenic differentiation and cartilage regeneration, AALG-CS hydrogels were investigated in vitro and in vivo. Our study presented this injectable 3D AALG-CS hydrogel culture system by testing BMSCs growth and chondrogenic differentiation in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D scaffold produces a biomimetic environment for cell growth and promotes cell amplification, differentiation, and osteogenic gene expressions for bone regeneration. [61][62][63][64][65][66] When the ADSCs grow in the layer-by-layer paper-stacking 3D scaffolds, they have more osteogenic gene expressions.…”
mentioning
confidence: 99%